Numerical Analysis of Thermal Gradient & Magnetic Field using Ferrofluid Cooling - Garg, Harry; Singh, Sahib; Negi, Vipender Singh; Kharola, Ashish Singh; Lall, Arun K. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Ferrofluid is a colloidal suspension of single domain magnetic particles of diameter approximately 10 nm, coated with a molecular layer of a dispersant and suspended in a liquid carrier. Ferrofluids may form the basis for next generation noiseless, vibration free passive cooling technique. The pumping ability of ferrofluid depends on temperature gradient and magnetic field orientation. The proposed work covers numerical analysis of heat transfer, magnetism and flow characteristics of ferrofluids. Thermal conductivity and viscosity of ferrofluid governs the heat transfer and flow characteristics. The variation of flow with the direction of magnetic field has been investigated in this paper.